1982
DOI: 10.1001/archderm.118.7.474
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced percutaneous penetration with 1-dodecylazacycloheptan-2-one

Abstract: 1-Dodecylazacycloheptan-2-one (Azone) is a new agent that enhances the percutaneous absorption of a number of different chemicals. This report delineates the enhancement of penetration of clindamycin phosphate, erythromycin base, fusidate sodium, fluorouracil, desonide, amcinonide, and triamcinolone acetonide. For this purpose 1-dodecylazacycloheptan-2-one can be used in concentrations as low as 1%. It is colorless, relatively odorless, nontoxic, and can be applied neat to human skin without any irritation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

1985
1985
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…If these chemical penetration enhancers were to be used in oral mucosal drug delivery, their safety and potential for irritancy would require some investigation. Early literature did suggest that AZ produces minimal irritation on mucous membranes or skin when applied neat31; however, more recent studies have demonstrated that AZ has the potential to cause irritation and some tissue damage when applied to the skin,32,33 rectal mucosa,34 and cornea 35,36. It is possible, therefore, that AZ may cause some irritation to the buccal mucosa, and so further investigation on this aspect is required.…”
Section: Discussionmentioning
confidence: 99%
“…If these chemical penetration enhancers were to be used in oral mucosal drug delivery, their safety and potential for irritancy would require some investigation. Early literature did suggest that AZ produces minimal irritation on mucous membranes or skin when applied neat31; however, more recent studies have demonstrated that AZ has the potential to cause irritation and some tissue damage when applied to the skin,32,33 rectal mucosa,34 and cornea 35,36. It is possible, therefore, that AZ may cause some irritation to the buccal mucosa, and so further investigation on this aspect is required.…”
Section: Discussionmentioning
confidence: 99%
“…Azones have been widely studied: it is believed that their mechanism of action is to act as a solvent of the lipids of the skin, denaturing proteins and modifying the drug diffusion coefficient in the process of permeation through the skin. Several studies have been conducted in which azone increases the permeation of compounds such as antifungal, antimicrobial, triamcinolone, and other corticosteroids, reporting in some cases, irritation problems [ 26 , 51 , 52 ]. The alkanes exert their promoter effect by being slightly irritating, extensively altering the stratum corneum, and therefore, the barrier function of the epidermis.…”
Section: Discussionmentioning
confidence: 99%
“…Further support for the contention that laurocapram optimizes triamcinolone's activity is provided by the observation that the clinical activity of a given corticosteroid can vary widely depending on the formulation, 20 for example that the various triamcinolone acetonide preparations vary from Class III to Class VI potency 11 . It is worth noting that, in addition to laurocapram, the TNX formulation also contains the common solvent propylene glycol, shown to act synergistically with laurocapram with regard to penetration enhancement 12,13 , 21–24 .…”
Section: Discussionmentioning
confidence: 99%
“…Laurocapram (1‐dodecylazacycloheptan‐2‐one) has shown promise as an enhancer of percutaneous penetration of a variety of hydrophilic and lipophilic drugs, including antimicrobials, antifungals, and corticosteroids in human and animal models 10,11 , 12 . It is thought to increase the fluidity of the lipid bilayer in the stratum corneum, 13,14 , 15 thus facilitating the permeation of lipophilic drugs such as triamcinolone.…”
Section: Introductionmentioning
confidence: 99%